The supramolecular derivatisation of pharmaceutically relevant compounds via co-crystallization and cyclodextrin inclusion complexation - Vicatos, Alexios Ivan (Department of Chemistry, 2023)
The supramolecular derivatisation of pharmaceutically relevant compounds via co-crystallization and cyclodextrin (CD) inclusion complexation was attempted in order to produce new solid forms of these compounds for potential pharmaceutical applications. The pharmaceutically relevant compounds investigated included (a) three drug leads, namely pyrido[1,2-a]benzimidazole derivatives [displaying activity against schistosomiasis (bilharzia)], (b) two steroidal compounds, namely -estradiol (used for hormonal therapy and treatment of breast and prostate cancer), and progesterone (used for hormonal therapy), and (c) the potent antioxidant pterostilbene (displaying anti-cancer activity inter alia). Six new solid forms of the pyrido[1,2-a]benzimidazole derivatives resulted from their interaction with partner molecules L-malic acid and nicotinamide using 1:1 molar ratios of the starting materials. They were characterised by powder X-ray diffraction, thermal analysis and spectroscopic (FT-IR and 1H NMR) techniques. Preliminary solubility studies indicated that for five of the forms, aqueous solubility increases for the drug leads in the range 2- to 20-fold were achieved. In addition, amorphous forms of the three pyrido[1,2-a]benzimidazole derivatives were prepared via grinding and also assessed for aqueous solubility improvement, with the result that only one of them indicated a 2-fold aqueous solubility increase. In addition, nine new hydrated CD inclusion complexes with guests -estradiol (BES), progesterone (PRO) and pterostilbene (PTB), were isolated using kneading and/or co-precipitation methods, and analysed using thermal analysis, powder X-ray diffraction and 1H NMR analytical techniques. The CD inclusion complexes (with host-guest stoichiometries in parentheses) included -CD·BES (2:1), - CD·BES (1:1), dimethylated -CD·BES (1:1), -CD·PRO (2:1), -CD·PRO (3:2), dimethylated -CD·PRO (1:1), -CD·PTB (1:1), -CD·PTB (1:1) and permethylated -CD·PTB (1:1). The -CD·BES, -CD·BES, - CD·PRO and -CD·PRO inclusion complexes were assessed for their ability to improve the aqueous solubility of the respective steroids at 27 o C. The SAPI(CD)/SAPI ratios for these CD complexes (SAPI(CD) indicating the solubility of each steroid in the form of the CD complex and SAPI the solubility of the pure steroid), were 21.3  0.1, 6.1  0.3, 5.5  0.1 and 19.9  0.1 respectively, thus indicating that CD inclusion complexation increased the aqueous solubility of both steroids. Phase solubility studies of pterostilbene (PTB) with sulfobutylether -CD (SBEBCD) and randomly methylated -CD (RAMEB), indicated that the low aqueous solubility of PTB could be enhanced by factors of 1431 and 1356 respectively using 20 mM concentrations of SBEBCD and RAMEB at 25 o C. Single-crystal Xray structures of six of the new CD inclusion complexes were elucidated, -CD·BES, -CD·PRO and - CD·PRO featuring severely disordered guest molecules, while analysis of -CD·PTB, DMB·BES and DMB·PRO revealed the detailed modes of guest inclusion of the respective drugs unequivocally.